СLINICAL CHARACTERISTICS OF CHILDREN AND ADOLESCENTS WITH METABOLIC SYNDROME IN KYIV - Maiia Aliusef; Alina Churylina (Acta Medica Leopoliensia)
This study aimed to clinically evaluate children and adolescents with metabolic syndrome (MetS) in order to identify and diagnose the condition at an early stage and prevent possible complications.